Game analysis of decreasing generation cost characteristics in electricity spot market. Issue 1 (February 2021) - Lu, Zhanhui; Jing, Zhaoxia
Abstract: The construction of Chinese electricity spot market is in its infancy. Market rules have borrowed from foreign mature market experiences, adopted marginal electricity price settlement mechanisms, and stipulated that the biddings on the power generation side will increase monotonously. However, there are thermal power generating units in China whose marginal cost does not meet the characteristics of monotonous increase. In this context, studying the strategic behaviour of thermal power generating units with diminishing marginal cost characteristics in the market, highlighting the impact of existing rules on market participants' decision making, is of great significance to the design and operation of Chinese electricity spot market. First, an existing generation market clearing model based on monotonically increasing quotes and a strategy model for generating units based on monotonically decreasing marginal costs are established. Then, the above models are organically combined to form a bilevel optimization model, and the iterative optimization is performed to obtain a market equilibrium solution. Finally, a numerical example is used to clearly describe the bidding strategy of the unit in the spot market, and the incentive effects of market regulations on its bidding behaviour are discussed.